Students’ Demotivating Factors in English Language Learning at One State Madrasah Tsanawiyah in Palembang, South Sumatera, Indonesia - DIAN ERLINA; DETA DESVITASARI; LENNY MARZULINA; ALMIRAH MEIDA RISFINA (Indonesian Research Journal in Education |IRJE|, 2020)
This research investigated students' demotivating factors in English language learning at MTsN 1 Palembang. The research was in the form of case study research design. The participants were the second-grade students at MTsN 1 Palembang. Based on their English achievement, there were 11 students being demotivated in learning English. The data were gained by using document review and face-to-face interviews. The data from document review and interview were analyzed by using thematic analysis. The findings showed that there were five demotivating factors in English language learning: (a) inadequate school facilities, (b) lack of teachers' competence and teaching styles, (c) learning content and materials, (d) classroom condition and classmates' attitudes, and (e) lack of self-confidence. Keywords: demotivation, demotivating factors, English language learning